Development of digital teaching material in the South Sumatra traditional games course - Taruni Suningsih; Rukiyah Rukiyah; Rindang Senja Andarini (Jurnal Inovasi Teknologi Pendidikan, 2023)
The advances in technology and information development are increasingly rapid is a great potential that learners can utilize to improve the quality of learning. It is consistent with the characteristic of students as active users of digital technology. So, lecturers need to make updates to improve the quality of learning. One of them is by providing teaching material according to the needs of students. This study aims to develop digital teaching material for the South Sumatra Traditional Games course at the Study Program of Early Childhood Education Teacher Education, Faculty of Teacher Training and Education, Sriwijaya University. This study used the ADDIE Research and Development (RD) method with five stages: analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through interviews, questionnaires, and tests. Data analysis techniques using quantitative and qualitative data analysis. The results showed that the evaluation of digital teaching material products that experts had carried out showed that the material aspect scored 87,5% in the Very Good category, the language aspect scored 85% in the Very Good category, and the media aspect scored 92,5% in the Very Good category. Based on this evaluation, it can be concluded that the digital teaching material in the developed South Sumatra Traditional Games courses are valid, feasible, and practical to be used in the learning process. Research can be continued by developing interactive digital teaching material.